Irrigation technologies, Use of Solar Pumps and Gendered Impacts - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The CGIAR Nexus Gains initiative supported a survey on irrigation solar pumps in Uganda to examine how solar pump ownership impacts the livelihoods of women and men in rural areas. This questionnaire was utilized to collect data from both beneficiaries and non-beneficiaries of the World Bank solar pump subsidy project, implemented by the Ugandan Ministry of Agriculture, Fisheries, and Animal Industry.